Alpha-olefin interpolymers with improved molecular design for photovoltaic encapsulants

By using ethylene/α-olefin interpolymer and peroxide curing packages in photovoltaic encapsulator materials, the problems of insufficient fluidity and cross-linking reaction decomposition at high temperatures are solved, and improved curing performance and extrusion are achieved. improves the stability and production efficiency of materials.

CN114867759BActive Publication Date: 2025-02-07DOW GLOBAL TECHNOLOGIES LLC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202080090219.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-26
Filing Date
2020-12-17
Publication Date
2025-02-07
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

Existing photovoltaic encapsulator materials are insufficient in fluidity at high temperatures, resulting in unstable electronic components and wiring during testing and use, and the use of peroxide cured packages leads to the decomposition of cross-linking reactions during low-temperature extrusion, affecting production efficiency and cost.

Method used

Using ethylene/α-olefin interpolymers, a TGIC with high total unsaturation, narrow molecular weight distribution and suitable TGICs are prepared by polymerizing ethylene, α-olefins, solvents and metal complexes in the reactor at ≥150°C. The width parameter of polymer, combining peroxide and silane coupling agent to promote crosslinking reaction.

Benefits of technology

Improved curing performance and good extrusionability are achieved, improved adhesion to glass is provided, problems of insufficient high-temperature fluidity and cross-linking reaction decomposition are solved, and production efficiency and material properties are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005138611770000011
    Figure FDA0005138611770000011
  • Figure FDA0005138611770000041
    Figure FDA0005138611770000041
  • Figure GDA0004813767320000031
    Figure GDA0004813767320000031
Patent Text Reader

Abstract

The present invention provides a composition comprising an ethylene / α-olefin interpolymer, wherein the interpolymer comprises the following properties: a) total unsaturation / 1000C ≥ 0.30; b) molecular weight distribution (MWD) ≤ 3.0; c) TGIC width parameter B 1 / 4 ≤8.0. A solution polymerization process for preparing an ethylene / α-olefin interpolymer; the process comprises polymerizing a reaction mixture comprising ethylene, an α-olefin, a solvent, and a metal complex as described herein in a reactor at a reactor temperature of ≥150°C. A method for determining the TGIC width parameter B of a polymer composition 1 / x The method comprises a polymer composition comprising one or more olefin-based polymers.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to provisional application PCT / CN2019 / 128574 filed on December 26, 2019, the entire text of which is incorporated herein by reference. Background Art

[0003] Polymers designed for photovoltaic encapsulants must meet many requirements. In order to prevent electronic components and wiring from moving during qualification testing and use, polymer materials must not flow significantly at temperatures up to 85°C. One way to achieve this is to include semi-crystalline polymers with melting points above this temperature. However, other encapsulation material requirements, such as high optical transparency and low modulus, are optimized using low crystallinity polymers. In order to balance these requirements, low crystallinity polymers such as ethylene-vinyl acetate copolymers (EVA) or polyolefin elastomers (POE) are usually combined with peroxide-based reactive curing packages. Low crystallinity polymers provide high transparency and low modulus, while the curing package promotes cross-linking reactions that form a network of polymers, thereby providing mechanical stability at high temperatures. This cross-linking reaction occurs during module lamination, usually at 150°C.

[0004] The inclusion of this peroxide cure package creates an additional design conflict because the film extrusion process must be carried out at low temperatures to prevent the peroxide from decomposing in the extruder and initiating a crosslinking reaction. The heat generated during extrusion is related to the extrusion rate and polymer viscosity; high viscosity and high extrusion rates generate more heat. Therefore, in order to extrude peroxide cure compositions, low viscosity resins extruded at low rates are preferred. However, low extrusion rates are economically disadvantageous, and low viscosity is usually achieved by using low molecular weight resins. Typically, low molecular weight resins cannot be effectively crosslinked, and in order to achieve the necessary crosslinking levels, higher peroxide cure package loadings or longer times are required during the module lamination process. Both solutions are expensive and inefficient.

[0005] New polymers that are extruded at high rates and highly crosslinked, each relative to conventional polymers for photovoltaic encapsulants. EP2958151B1 discloses resin compositions for solar cell encapsulants, which are disclosed as having good crosslinking, good heat resistance and good transparency. The resin composition contains an ethylene / α-olefin copolymer that satisfies the following relationship: N×V≥10, where N is the number of branches derived from the comonomer, and V is the total number of vinyl and vinylidene groups in the copolymer (see, for example, paragraphs

[0030] and

[0031] ). Here, V is greater than or equal to 0.17. See also JP2012009688A (machine translation), which discloses a solar sealing composition containing an ethylene / α-olefin copolymer, the copolymer having a total unsaturation amount of 0.22 (vinyl, vinylidene, cis- and trans-vinylene, trisubstituted vinylene); a density of 0.860 g / cc to 0.920 g / cc; and an Mz / Mn of less than or equal to 8.0. Additional polymer compositions for solar encapsulants are disclosed in the following references: EP2637217B1 (compositions containing ethylene / α-olefin copolymers, the copolymers comprising in part an MFR of 2 to less than 10, a density of 0.865 g / cc to 0.884 g / cc, and a Shore A hardness of 60 to 85; and wherein the MWD may be 1.2 to 3.5), and US8581094 (compositions containing polyolefin copolymers, the copolymers comprising in part a density of less than about 0.90 g / cc, a melting point of less than about 95°C, and a 2% secant modulus of less than about 150 Mega-Pascal). However, these references do not promote new resin designs to achieve high extrusion rates and high crosslinking. There remains a need for such compositions that promote high extrusion rates and high crosslinking. This need has been met by the present invention. Summary of the invention

[0006] A composition comprising an ethylene / α-olefin interpolymer comprising the following properties:

[0007] a) Total unsaturation / 1000C ≥ 0.30;

[0008] b) Molecular weight distribution (MWD) ≤ 3.0;

[0009] c) TGIC width parameter B 1 / 4 ≤8.0.

[0010] A solution polymerization process for preparing ethylene / α-olefin interpolymers; the process comprises polymerizing a reaction mixture comprising ethylene, an α-olefin, a solvent and a metal complex selected from the following a) in a reactor at a reactor temperature of ≥150°C:

[0011] a) a biphenol metal complex selected from the following structure 1:

[0012]

[0013] Structure 1, wherein:

[0014] M is Zr or Hf, the metal being in a formal oxidation state of +2, +3 or +4;

[0015] n is 0, 1 or 2;

[0016] When n is 1, X is a monodentate ligand or a bidentate ligand;

[0017] When n is 2, each X is an independently selected monodentate ligand;

[0018] The metal complex is generally charge neutral;

[0019] -Z 1 -and-Z 2 -, each of which is independently selected from -O-, -S-, -N(R N )-or-P(R P )-;

[0020] R 1 and R 8 Independently selected from the group consisting of: -H, (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2.-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R)-、(R C )2NC(O)-, halogen, a group having the formula (I), a group having the formula (II) and a group having the formula (III):

[0021]

[0022] Where R 31–35 , R 41-48 and R 51-59 Each of which is independently selected from (C1-C 40) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2, -N=CHR C 、-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R C )2NC(O)-, halogen or -H;

[0023] Where R 2-7 , R 9-16 Each of which is independently selected from (C1-C 40 )alkyl, (C1-C40)heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2, -N=CHR C 、-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R C )2NC(O)-, halogen or -H;

[0024] L is (C1-C 40 )alkylene or (C1-C 40 )heteroalkylene, wherein the (C1-C 40 ) an alkylene group having a linker backbone portion comprising 1 to 10 carbon atoms, connecting two Z groups in structure 1 (L being bonded to the two Z groups); or (C1-C 40 ) heteroalkylene has a linker backbone portion including 1 to 10 atoms, connecting the two Z groups in Structure 1, wherein (C1-C40 ) wherein 1 to 10 atoms of the heteroalkylene group are connected to each of the 1 to 10 atoms of the main chain and each of the atoms is independently a carbon atom or a heteroatom group, wherein each heteroatom group is independently O, S, S(O), S(O)2, Si(R C )2、Ge(R C 2. P(R C ) or N(R C ); and each R in structure 1 C , R P and R N Independently (C1-C 30 ) hydrocarbon group, (C1-C 30 ) heteroalkyl or -H.

[0025] A method for determining the TGIC width parameter B of a polymer composition 1 / x The method comprises the following steps:

[0026] a) dissolving the polymer composition in an organic solvent to form a polymer solution;

[0027] b) injecting at least a portion of the polymer solution onto a column comprising a support material comprising graphite;

[0028] c) cooling the support material at a rate greater than or equal to 0.1° C. / min;

[0029] d) increasing the temperature of the support material to elute the polymer of the polymer composition;

[0030] e) Generate a "dwi / dT versus temperature" curve;

[0031] f) For the maximum height of the curve (dwi / dTi versus temperature), calculate the width of the curve at 1 / x of the maximum height, where x>1;

[0032] g) determine the temperature at which the curve has the maximum height (Tp);

[0033] h) calculating the HDPE peak width at 1 / x of the HDPE peak height (peak width @ 1 / x) based on an eicosane / iPP / HDPE reference (at an elution temperature of 150.0°C); and wherein the reference is analyzed by TGIC according to steps a) to g);

[0034] i) Calculate B based on the following equation 1 / x :

[0035] BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Extrapolation of the elution temperature of the TGIC temperature calibration is depicted. The solid line is the experimental data and the dashed line is the extrapolation of the elution temperature of the two isothermal steps.

[0037] Figure 2 is the TGIC chromatogram of the eicosane / iPP / HDPE mixture.

[0038] Figure 3 The elution peak temperature (Tp) of ethylene-octene copolymers is plotted versus octene weight percent.

[0039] Figure 4 It is the TGIC curve of POE (POE A) of the present invention.

[0040] Figure 5 This is the TGIC curve for comparison with POE (POE C). DETAILED DESCRIPTION

[0041] Ethylene / α-olefin interpolymer designs have been discovered that provide improved cure properties and good extrudability. It has also been discovered that a higher vinyl fraction in the total unsaturation and a narrow comonomer distribution in the interpolymer provide improved adhesion to glass.

[0042] As discussed above, a composition is provided, the composition comprising an ethylene / α-olefin interpolymer, the interpolymer comprising the following properties:

[0043] a) Total unsaturation / 1000C ≥ 0.30;

[0044] b) Molecular weight distribution (MWD) ≤ 3.0;

[0045] c) TGIC width parameter B 1 / 4 ≤8.0.

[0046] The above composition may comprise a combination of two or more embodiments as described herein.The ethylene / α-olefin interpolymer may comprise a combination of two or more embodiments as described herein.

[0047] The above TGIC width parameter B 1 / 4 is an indication of the breadth of the comonomer distribution of the ethylene / α-olefin interpolymer. 1 / 4 In one embodiment or a combination of two or more embodiments (each described herein), the TGIC width parameter B is 1 / 4≤7.5, or ≤7.0, or ≤6.5, or ≤6.0, or ≤5.5, or ≤5.0, or ≥4.8, or ≤4.6, or ≤4.4, or ≤4.2, or ≤4.0, or ≤3.8. In one embodiment or a combination of two or more embodiments (each of which is described herein), the TGIC width parameter B 1 / 4 ≥1.5, or ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.2.

[0048] In one embodiment or a combination of two or more embodiments (each of which is described herein), the ethylene / α-olefin interpolymer has a density ≥ 0.860 g / cc, or ≥ 0.861 g / cc, or ≥ 0.862 g / cc, or ≥ 0.863 g / cc, or ≥ 0.864 g / cc, or ≥ 0.865 g / cc, or ≥ 0.866 g / cc, or ≥ 0.867 g / cc, or ≥ 0.868 g / cc, or ≥ 0.869 g / cc, or ≥ 0.870 g / cc (1 cc = 1 cm 3 In one embodiment or a combination of two or more embodiments (each of which is described herein), the ethylene / α-olefin interpolymer has a density of ≤ 0.900 g / cc, or ≤ 0.890 g / cc, or ≤ 0.888 g / cc, or ≤ 0.886 g / cc, or ≤ 0.885 g / cc, or ≤ 0.884 g / cc, or ≤ 0.883 g / cc, or ≤ 0.882 g / cc, or ≤ 0.880 g / cc, or ≤ 0.878 g / cc.

[0049] In one embodiment or a combination of two or more embodiments (each of which is described herein), the total unsaturation / 1000C of the ethylene / α-olefin interpolymer is ≥ 0.32, or ≥ 0.35, or ≥ 0.40, or ≥ 0.45, or ≥ 0.50, or ≥ 0.52, or ≥ 0.54, or ≥ 0.56. In one embodiment or a combination of two or more embodiments (each of which is described herein), the total unsaturation / 1000C of the ethylene / α-olefin interpolymer is ≤ 1.00, or ≤ 0.95, or ≤ 0.90, or ≤ 0.85, or ≤ 0.80, or ≤ 0.78, or ≤ 0.76, or ≤ 0.74, or ≤ 0.72, or ≤ 0.70.

[0050] In one embodiment or a combination of two or more embodiments (each of which is described herein), the ethylene / α-olefin interpolymer has a molecular weight distribution (MWD=Mw / Mn) of ≥1.6, or ≥1.7, or ≥1.8, or ≥1.9, or ≥2.0. In one embodiment or a combination of two or more embodiments (each of which is described herein), the ethylene / α-olefin interpolymer has a molecular weight distribution MWD of ≤2.9, or ≤2.8, or ≤2.7, or ≤2.6, or ≤2.5, or ≤2.4, or ≤2.3, or ≤2.2.

[0051] In one embodiment or a combination of two or more embodiments (each described herein), the interpolymer further comprises ≥ 5.0×10 3 (g / mol), or ≥6.0×10 3 (g / mol), ≥7.0×10 3 (g / mol), ≥7.5×10 3 (g / mol), or ≥8.0×10 3 (g / mol), or ≥8.5×10 3 (g / mol), or ≥9.0×10 3 (g / mol), or ≥9.5×10 3 (g / mol), or ≥10×10 3 In one embodiment or a combination of two or more embodiments (each of which is described herein), the interpolymer further comprises ≤30×10 3 (g / mol), or ≤20×10 3 (g / mol), or ≤18×10 3 (g / mol), or ≤16×10 3 (g / mol), or ≤14×10 3 (g / mol), or ≤12×10 3 The product of [(vinyl / 1000C)*(Mn)] in g / mol.

[0052] In one embodiment or a combination of two or more embodiments (each of which is described herein), the interpolymer further comprises a ratio of [(vinyl / 1000C) / (vinylidene / 1000C)] of ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.1, or ≥3.2, or ≥3.3, or ≥3.4. In one embodiment or a combination of two or more embodiments (each of which is described herein), the interpolymer further comprises a ratio of [(vinyl / 1000C) / (vinylidene / 1000C)] of ≤6.0, or ≤5.5, or ≤5.0, or ≤4.8, or ≤4.6, or ≤4.4, or ≤4.2, or ≤4.0, or ≤3.8.

[0053] In one embodiment or a combination of two or more embodiments (each of which is described herein), the ethylene / α-olefin interpolymer further comprises ≥50%, or ≥52%, or ≥54%, or 56%, or ≥58%, or ≥60%, or ≥62% % vinyl. % vinyl = [(vinyl / 1000C) / (total unsaturation / 1000C)] x 100.

[0054] In one embodiment or a combination of two or more embodiments (each of which is described herein), the composition further comprises a peroxide and a silane coupling agent. In one embodiment or a combination of two or more embodiments (each of which is described herein), the composition further comprises a crosslinking aid.

[0055] The present invention also provides an article comprising at least one component formed by a composition of any one embodiment or a combination of two or more embodiments described herein. In one embodiment or a combination of two or more embodiments (each embodiment is described herein), the article is a film. In one embodiment or a combination of two or more embodiments (each embodiment is described herein), the article is a solar cell module.

[0056] The ethylene / α-olefin interpolymer comprises ethylene and α-olefin in polymerized form. The α-olefin can be an aliphatic or aromatic compound. The α-olefin is preferably C3-C 20 Aliphatic compounds, preferably C3-C 16 Aliphatic compounds, and more preferably C3-C 10 Aliphatic compounds. Preferred C3-C 10 The aliphatic α-olefins include propylene, 1-butene, 1-hexene, 1-octene and 1-decene, and more preferably 1-octene.

[0057] The peroxide (containing at least one "-OO-" group) is preferably an organic peroxide, for example, tert-butyl peroxycarbonate-2-ethylhexyl ester; di-tert-butyl peroxide; tert-butyl peroxide isopropyl benzene; diisopropyl benzene peroxide; 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; di(tert-butylperoxyisopropyl)benzene; tert-butyl peroxybenzoate; 1,1-di(tert-butylperoxy)-3,3,5-trimethyl- Cyclohexane; 2,5-dimethyl-2,5-di(tert-amyl peroxy)hexane; 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexyne-3, 2,5-dimethyl-2,5-di(tert-amyl peroxy)hexyne-3; di-tert-amyl peroxide; 1,3-dimethyl-3-(tert-butyl peroxy)butanol; 1,3-dimethyl-3-(tert-amyl peroxy)butanol; and mixtures of two or more of these initiators. See, for example, TRIGONOX peroxide from AkzoNobel, LUPEROX peroxide from ARKEMA.

[0058] Silane coupling agents include, but are not limited to, vinyl trimethoxysilane and 3-(trimethoxysilyl)propyl methacrylate. Cross-linking aids include, but are not limited to, triallyl cyanurate, triallyl phosphate, triallyl isocyanurate, and 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane. The composition of the present invention may further include one or more additives, such as UV stabilizers, antioxidants, and combinations thereof.

[0059] In one embodiment or a combination of two or more embodiments (each of which is described herein), the inventive composition further comprises a thermoplastic polymer that differs from the ethylene / α-olefin interpolymer in one or more characteristics, such as monomer type and / or amount, Mn, Mw, Mz, MWD, V0.1, V100, RR (V0.1 / V100), or any combination thereof. Polymers include, but are not limited to, ethylene-based polymers, propylene-based polymers, and olefin multi-block interpolymers. Suitable ethylene-based polymers include, but are not limited to, linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), ultra low density polyethylene (ULDPE), homogeneously branched linear ethylene-based polymers, and homogeneously branched substantially linear ethylene-based polymers (i.e., homogeneously branched long chain branched ethylene polymers). Examples of propylene-based polymers include polypropylene homopolymers and propylene / ethylene copolymers.

[0060] Also provided is a solution polymerization process for preparing an ethylene / α-olefin interpolymer; the process comprises polymerizing a reaction mixture comprising ethylene, an α-olefin, a solvent and a metal complex selected from structure 1 in a reactor at a reactor temperature of ≥150°C, as described in the Summary of the Invention (SOI) above.

[0061] The inventive method may comprise a combination of two or more embodiments as described herein. The biphenol metal complex may comprise a combination of two or more embodiments as described herein. As used herein, R1=R 1 , R2=R 2 , R3=R 3 , and so on. In addition, the symbol R a(1) -R a(n) , where "a(1) to a(n)" represent consecutive numbers, referring to R a(1) , R a(2) , R a(3) ,……,R a(n) For example, R 31 -R 35 Refers to R 31 , R 32 , R 33 , R 34 , R 35 ; and R 51 -R 59 Refers to R 51 , R 52 , R 53 , R 54 , R 55 , R 56 , R 57 , R 58 , R 59 In each of formulae (I) to (III), the wavy line represents the respective formula (R 1 or R 8 The connection (bond) between the phenol group and the rest of the biphenol metal complex.

[0062] In one embodiment or a combination of two or more embodiments (each of which is described herein), for Structure 1, L is -(CH2) n -, where n = 2 to 4. –CH2C(R a R b )CH2-, where R a and R b Each independently is (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl or -H; or -CH2Ge(R D )2CH2- or –CH2Si(RD )2CH2-, where each R D Independently selected from the group consisting of: -H, (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2.-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )- and (R N )2NC(O)-, and each R in structure 1 C , R P and R N Independently (C1-C 30 ) hydrocarbon group, (C1-C 30 ) heteroalkyl or -H.

[0063] In one embodiment or a combination of two or more embodiments (each of which is described herein), for Structure 1, L is -CH2C(R a R b )CH2-, where R a and R b Each independently is (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl or -H; or -CH2Ge(R D )2CH2- or –CH2Si(R D )2CH2-, where each R D Independently selected from the group consisting of: -H, (C1-C 40 ) alkyl and (C1-C 40 ) heteroalkyl.

[0064] In one embodiment or a combination of two or more embodiments (each of which is described herein), for Structure 1, -Z 1 -and-Z 2 Each of - is -O-.

[0065] In one embodiment or a combination of two or more embodiments (each of which is described herein), for Structure 1, R 1 and R 8 are the same and are selected from the group consisting of a group having formula (I), a group having formula (II) and a group having formula (III), and are further selected from a group having formula (II).

[0066] In one embodiment or a combination of two or more embodiments (each of which is described herein), for Structure 1, n=2, and each X is the same and is an unsubstituted alkyl.

[0067] In one embodiment or a combination of two or more embodiments (each described herein), the reaction mixture further comprises a co-catalyst-1 comprising a borate and a co-catalyst-2 comprising an aluminoxane.

[0068] In one embodiment or a combination of two or more embodiments (each of which is described herein), the process has an overall catalyst efficiency of ≥2.5×10-1 at a reactor temperature of ≥155°C, or ≥160°C, or ≥165°C, or ≥170°C, or ≥175°C, or ≥180°C, or ≥185°C, or ≥186°C, or 187°C, or ≥188°C, or ≥189°C, or ≥190°C. 6 , or ≥2.6×10 6 , or ≥2.8×10 6 , or ≥3.0×10 6 , or ≥3.2×10 6 , or ≥3.4×10 6 , or ≥3.6×10 6 , or ≥3.7×10 6 , or ≥3.8×10 6 , or ≥3.9×10 6 , or ≥4.0×10 6 , or ≥4.1×10 6 , or ≥4.2×10 6 [(g interpolymer) / (g total catalyst metal)].

[0069] In one embodiment or a combination of two or more embodiments (each of which is described herein), the method is carried out at 0.860 g / cc to 0.900 g / cc, or 0.865 g / cc to 0.890 g / cc, or 0.868 g / cc to 0.880 g / cc (1 cc = 1 cm 3 The total catalyst efficiency at the density of ethylene / α-olefin interpolymer of ≥2.5×10 6 , or ≥2.6×106 , or ≥2.8×10 6 , or ≥3.0×10 6 , or ≥3.2×10 6 , or ≥3.4×10 6 , or ≥3.6×10 6 , or ≥3.7×10 6 , or ≥3.8×10 6 , or ≥3.9×10 6 , or ≥4.0×10 6 , or ≥4.1×10 6 , or ≥4.2×10 6 [(g interpolymer) / (g total catalyst metal)].

[0070] In one embodiment or a combination of two or more embodiments, each of which is described herein, the process is carried out at a reactor temperature of ≥155°C, or ≥160°C, or ≥165°C, or ≥170°C, or ≥175°C, or ≥180°C, or ≥185°C, or ≥186°C, or 187°C, or ≥188°C, or ≥189°C, or ≥190°C. In one embodiment or a combination of two or more embodiments, each of which is described herein, the process is carried out at a reactor temperature of ≤250°C, or ≤240°C, or ≤230°C, or ≤220°C, or ≤210°C, or ≤200°C.

[0071] The term "substituent" refers to a substituent (R s ) replaces a hydrogen atom (-H) bonded to a carbon atom or heteroatom of the corresponding unsubstituted compound. The symbol "R S " refers to a heteroatom or a chemical group including at least one heteroatom. The term "substituted" means that at least one hydrogen atom (-H) bonded to a carbon atom or a heteroatom of the corresponding unsubstituted compound is replaced by a substituent (R s ) instead.

[0072] The term "heteroatom" refers to an atom other than hydrogen or carbon. The term "heteroatom group" refers to a heteroatom or a chemical group containing one or more heteroatoms. Examples of heteroatom groups include, but are not limited to, O, S, S(O), S(O)2, Si(R C )3. P(R P )2、N(R N )2. –N=C(R C )2、-Ge(R C )2- or –Si(R C )2–, where each R C and each R P are independently unsubstituted (C1-C30 )alkyl or -H, and each R N is unsubstituted (C1-C 30 ) hydrocarbon group.

[0073] The term "-H" means a hydrogen or a hydrogen group covalently bonded to another atom. "Hydrogen," H, and "-H" are interchangeable and have the same meaning unless expressly specified otherwise.

[0074] The term “(C1–C 40 )hydrocarbyl" means a hydrocarbon group having 1 to 40 carbon atoms, and the term "(C1-C 40 )alkylene group" means a hydrocarbon diradical having 1 to 40 carbon atoms, wherein each hydrocarbon group and each hydrocarbon diradical is aromatic or non-aromatic, saturated or unsaturated, straight chain or branched, cyclic (including monocyclic and polycyclic, fused and non-fused polycyclic, including bicyclic; 3 or more carbon atoms) or acyclic, and is unsubstituted or substituted with one or more R S replace.

[0075] The term "heterohydrocarbon" refers to a molecule or molecular backbone in which one or more carbon atoms are replaced by heteroatoms. 40 ) heteroalkyl" means a heteroalkyl group of 1 to 40 carbon atoms, and the term "(C1-C 40 The term "heteroalkylene" means a heteroalkyl diradical of 1 to 40 carbon atoms, each of which has one or more heteroatoms. The radical of the heteroalkyl group is located on a carbon atom or a heteroatom, and the diradical of the heteroalkyl group can be located on: (1) one or two carbon atoms, (2) one or two heteroatoms, or (3) both carbon atoms and heteroatoms. Each (C1-C 40 ) heteroalkyl and (C1–C 40 ) heteroalkylene may be unsubstituted or (substituted by one or more R S ) substituted, aromatic or non-aromatic, saturated or unsaturated, linear or branched, cyclic (including monocyclic and polycyclic, fused and non-fused polycyclic) or acyclic.

[0076] The term "halogen atom" or "halogen" refers to a group of a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), or an iodine atom (I). The term "halide" refers to the anionic form of a halogen atom: fluoride ion (F-), chloride ion (Cl-), bromide ion (Br-), or iodide ion (I-).

[0077] Also provided is a method for determining the TGIC width parameter B1 / x of a polymer composition comprising one or more olefin-based polymers; the method comprising the steps described above in SOI. The method may comprise a combination of two or more embodiments as described herein.

[0078] In one embodiment or a combination of two or more embodiments, each of which is described herein, the composition comprises ≥ 50 wt%, or ≥ 60 wt%, or ≥ 70 wt%, or ≥ 80 wt%, or ≥ 85 wt%, based on the weight of the composition, of one or more olefin-based polymers and further comprises ≥ 50 wt%, or ≥ 60 wt%, or ≥ 70 wt%, or ≥ 80 wt%, or ≥ 85 wt% of an ethylene-based polymer, further an ethylene / α-olefin interpolymer.

[0079] In one embodiment or a combination of two or more embodiments, each of which is described herein, the composition comprises ≥ 90 wt%, or ≥ 92 wt%, or ≥ 94 wt%, or ≥ 96 wt%, or ≥ 98 wt%, or ≥ 99 wt%, by weight of the composition, of one or more olefin-based polymers and further comprises ≥ 90 wt%, or ≥ 92 wt%, or ≥ 94 wt%, or ≥ 96 wt%, or ≥ 98 wt%, or ≥ 99 wt% of an ethylene-based polymer, further an ethylene / α-olefin interpolymer.

[0080] In one embodiment or a combination of two or more embodiments (each described herein), the composition comprises only one olefin-based polymer. In another embodiment, the olefin-based polymer is an ethylene / α-olefin interpolymer.

[0081] In one embodiment or a combination of two or more embodiments, each of which is described herein, the support material comprises ≥ 10 wt%, or ≥ 20 wt%, or ≥ 30 wt%, or ≥ 40 wt%, or ≥ 50 wt%, or ≥ 60 wt%, or ≥ 70 wt%, or ≥ 80 wt%, or ≥ 85 wt% graphite, based on the weight of the support material.

[0082] In one embodiment or a combination of two or more embodiments, each of which is described herein, the support material comprises ≥ 90 wt%, or ≥ 92 wt%, or ≥ 94 wt%, or ≥ 96 wt%, or ≥ 98 wt%, or ≥ 99 wt% graphite, based on the weight of the support material.

[0083] definition

[0084] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0085] As used herein, the term "composition" includes mixtures of materials including the composition as well as reaction products and decomposition products formed from the composition materials. Any reaction products or decomposition products are typically present in trace or residual amounts.

[0086] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Thus, the generic term polymer encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer, it being understood that trace amounts of impurities may be incorporated into the polymer structure) and the term interpolymer as defined below. Trace amounts of impurities (such as catalyst residues) may be incorporated into and / or within the polymer. Typically, polymers are stabilized with very small amounts ("ppm" amounts) of one or more stabilizers.

[0087] As used herein, the term "interpolymer" refers to polymers prepared by the polymerization of at least two different types of monomers. The term interpolymer thus includes the term copolymer (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.

[0088] As used herein, the term "olefin-based polymer" refers to polymers that contain, in polymerized form, 50 weight percent or majority weight percent olefins, such as ethylene or propylene (based on the weight of the polymer), and optionally may contain one or more comonomers.

[0089] As used herein, the term "propylene-based polymer" refers to a polymer that comprises, in polymerized form, a majority weight percent propylene (based on the weight of the polymer) and, optionally, may comprise one or more comonomers.

[0090] As used herein, the term "ethylene-based polymer" refers to a polymer that, in polymerized form, comprises 50 wt% or a majority weight percent ethylene (based on the weight of the polymer), and optionally may include one or more comonomers.

[0091] As used herein, the term "ethylene / α-olefin interpolymer" refers to a random interpolymer comprising, in polymerized form, 50 weight percent or majority weight percent ethylene (based on the weight of the interpolymer) and an α-olefin.

[0092] As used herein, the term "ethylene / a-olefin copolymer" refers to a random copolymer comprising, in polymerized form, 50 weight percent or a majority amount of ethylene monomer (based on the weight of the copolymer) and an a-olefin as the only two monomer types.

[0093] As used herein, the term "solution polymerization" refers to a polymerization process wherein the monomers as well as the produced polymer are dissolved in the polymerization solvent. In one embodiment, the reactor pressure is ≤ 1000 psig.

[0094] As used herein, the term "reaction mixture" refers to a mixture comprising one or more monomer types, a solvent and a metal complex. Typically, the reaction mixture also comprises one or more co-catalysts and hydrogen (H2).

[0095] As used herein, the term "total catalyst efficiency (units of 10^6 g polymer / g total catalyst metal)" with reference to a polymerization process refers to the production rate (e.g., lb / hr) of polymer formed during a polymerization process (or polymerization run) divided by the total feed rate (e.g., lb / hr) of catalyst metal (e.g., metal from one or more metal complexes) used during the same polymerization process (or polymerization run). Typically, polymerization is a steady-state process.

[0096] As used herein, the term "silane coupling agent" refers to a compound containing at least one "Si" atom and at least one "-CH2-" group and / or at least one "-CH3" group, and the compound forms a chemical bond between two materials; for example, a chemical bond between a polymer and an inorganic material.

[0097] As used herein, the term "solar cell (or photovoltaic cell)" refers to a device that converts solar radiation into electrical energy. Solar cells are typically presented in an array pattern.

[0098] As used herein, the term "solar cell module (or solar panel or solar module)" refers to a photovoltaic panel including a solar cell component.

[0099] As used herein, the terms "laminating," "lamination," and like terms refer to a process in which multiple layered materials are bonded together under conditions that include heat and pressure, and optionally a vacuum.

[0100] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not the components, steps, or procedures are specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.

[0101] List of some composition features

[0102] A] A composition comprising an ethylene / α-olefin interpolymer comprising the following properties:

[0103] a) Total unsaturation / 1000C ≥ 0.30;

[0104] b) Molecular weight distribution (MWD) ≤ 3.0;

[0105] c) TGIC width parameter B 1 / 4 ≤8.0.

[0106] B] A composition according to A] above, wherein the ethylene / α-olefin interpolymer has a density of ≥0.860 g / cc, or ≥0.861 g / cc, or ≥0.862 g / cc, or ≥0.863 g / cc, or ≥0.864 g / cc, or ≥0.865 g / cc, or ≥0.866 g / cc, or ≥0.867 g / cc, or ≥0.868 g / cc, or ≥0.869 g / cc, or ≥0.870 g / cc (1 cc = 1 cm 3 ).

[0107] C] A composition according to A] or B] above, wherein the ethylene / α-olefin interpolymer has a density of ≤0.900 g / cc, ≤0.890 g / cc, or ≤0.888 g / cc, or ≤0.886 g / cc, or ≤0.885 g / cc, or ≤0.884 g / cc, or ≤0.883 g / cc, or ≤0.882 g / cc, or ≤0.880 g / cc, or ≤0.878 g / cc.

[0108] D] A composition according to any one of A]-C] (A] to C]) above, wherein the total unsaturation / 1000C of the ethylene / α-olefin interpolymer is ≥ 0.32, or ≥ 0.35, or ≥ 0.40, or ≥ 0.45, or ≥ 0.50, or ≥ 0.52, or ≥ 0.54, or ≥ 0.56.

[0109] E] A composition according to any one of A] to D] above, wherein the total unsaturation / 1000C of the ethylene / α-olefin interpolymer is ≤1.00, or ≤0.95, or ≤0.90, or ≤0.85, or ≤0.80, or ≤0.78, or ≤0.76, or ≤0.74, or ≤0.72, or ≤0.70.

[0110] F] A composition according to any of A] - E] above, wherein the ethylene / α-olefin interpolymer further comprises a % vinyl group of ≥50%, or ≥52%, or ≥54%, or 56%, or ≥58%, or ≥60%, or ≤62%.

[0111] G] A composition according to any of A] - F] above, wherein the ethylene / α-olefin interpolymer further comprises a % vinyl group of ≤ 100%, or ≤ 95%, or ≤ 90%, or ≤ 85%, or ≤ 80%, or ≤ 78%, or ≤ 76%, or ≤ 74%, or ≤ 72%, or ≤ 70%, or ≤ 68%, or ≤ 66%.

[0112] H] A composition according to any one of A] to G] above, wherein the ethylene / α-olefin interpolymer further comprises ≥ 5.0×10 3 (g / mol), or ≥6.0×10 3 (g / mol), ≥7.0×10 3 (g / mol), ≥7.5×10 3 (g / mol), or ≥8.0×10 3 (g / mol), or ≥8.5×10 3 (g / mol), or ≥9.0×10 3 (g / mol), or ≥9.5×10 3 (g / mol), or ≥10×10 3 The product of [(vinyl / 1000C)*(Mn)] in g / mol.

[0113] I] A composition according to any one of A] to H] above, wherein the ethylene / α-olefin interpolymer further comprises ≤30×10 3 (g / mol), or ≤20×10 3 (g / mol), or ≤18×10 3 (g / mol), or ≤16×10 3 (g / mol), or ≤14×10 3 (g / mol), or ≤12×10 3 The product of [(vinyl / 1000C)*(Mn)] in g / mol.

[0114] J] A composition according to any one of A] to I] above, wherein the ethylene / α-olefin interpolymer further comprises a ratio of [(vinyl / 1000C) / (vinylidene / 1000C)] of ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.1, or ≥3.2, or ≥3.3, or ≥3.4.

[0115] K] A composition according to any one of A] to J] above, wherein the ethylene / α-olefin interpolymer further comprises a ratio of [(vinyl / 1000C) / (vinylidene / 1000C)] of ≤6.0, or ≤5.5, or ≤5.0, or ≤4.8, or ≤4.6, or ≤4.4, or ≤4.2, or ≤4.0, or ≤3.8.

[0116] L] A composition according to any one of A] to K] above, wherein the ethylene / α-olefin interpolymer further comprises an amount of (vinyl groups / 1000C) of ≥ 0.30, or ≥ 0.32, or ≥ 0.34, or ≥ 0.36.

[0117] M] A composition according to any one of A] to L] above, wherein the ethylene / α-olefin interpolymer further comprises a (vinyl / 1000C) amount of ≤ 0.60, or ≤ 0.58, or ≤ 0.56, or ≤ 0.54.

[0118] N] A composition according to any one of A] to M] above, wherein the ethylene / α-olefin interpolymer further comprises an amount of (vinylidene / 1000C) of ≥ 0.06, or ≥ 0.08, or ≥ 0.10.

[0119] O] A composition according to any one of A]-N] above, wherein the ethylene / α-olefin interpolymer further comprises an amount of (vinylidene / 1000C) of ≤0.20, or ≤0.18, or ≤0.16. P] A composition according to any one of A]-O] above, wherein the ethylene / α-olefin interpolymer further comprises a sum of [(vinylene / 1000C)+(vinylidene / 1000C)] of ≥0.42, or ≥0.44, or ≥0.46.

[0120] Q] A composition according to any one of A] to P] above, wherein the ethylene / α-olefin interpolymer further comprises a sum of [(vinyl / 1000C)+(vinylidene / 1000C)] of ≤ 0.61, or ≤ 0.60, or ≤ 0.59.

[0121] R] A composition according to any one of A] to Q] above, wherein the melt index (I2) of the ethylene / α-olefin interpolymer is ≥ 2.0 g / 10 min, or ≥ 4.0 g / 10 min, or ≥ 6.0 g / 10 min, or ≥ 8.0 g / 10 min, or ≥ 10.0 g / 10 min, or ≥ 12.0 g / 10 min, or ≥ 14.0 g / 10 min, or ≥ 15.0 g / 10 min.

[0122] S] A composition according to any one of A] to R] above, wherein the melt index (I2) of the ethylene / α-olefin interpolymer is ≤60 g / 10 min, or ≤50 g / 10 min, or ≤45 g / 10 min, or ≤40 g / 10 min, or ≤38 g / 10 min, or ≤36 g / 10 min, or ≤34 g / 10 min, or ≤32 g / 10 min.

[0123] T] A composition according to any one of A] to S] above, wherein the I10 / I2 of the ethylene / α-olefin interpolymer is ≥5.0, or ≥5.5, or ≥6.0, or ≥6.2, or ≥6.4, or ≥6.6, or ≥6.8, or ≥7.0, or ≥7.2, or ≥7.4, or ≥7.6.

[0124] U] A composition according to any one of A] to T] above, wherein the I10 / I2 of the ethylene / α-olefin interpolymer is ≤30.0, or ≤25.0, or ≤20.0, or ≤15.0, or ≤10.0, or ≤9.0, or ≤8.8, or ≤8.6, or ≤8.4, or ≤8.2, or ≤8.0.

[0125] V] A composition according to any of A] to U] above, wherein the ethylene / α-olefin interpolymer has a number average molecular weight Mn ≥ 12,000 g / mol, or ≥ 14,000 g / mol, or ≥ 16,000 g / mol, or ≥ 18,000 g / mol, or ≥ 20,000 g / mol, or ≥ 22,000 g / mol, or ≥ 24,000 g / mol.

[0126] W] A composition according to any one of A] to V] above, wherein the number average molecular weight Mn of the ethylene / α-olefin interpolymer is ≤50,000 g / mol, or ≤45,000 g / mol, or ≤40,000 g / mol, or ≤38,000 g / mol, or ≤36,000 g / mol, or ≤34,000 g / mol, or ≤32,000 g / mol, or ≤30,000 g / mol.

[0127] X] A composition according to any one of A] to W] above, wherein the weight average molecular weight Mw of the ethylene / α-olefin interpolymer is ≥38,000 g / mol, or ≥40,000 g / mol, or ≥42,000 g / mol, or ≥44,000 g / mol, or ≥46,000 g / mol, or ≥48,000 g / mol, or ≥50,000 g / mol.

[0128] Y] A composition according to any one of A] to W] above, wherein the weight average molecular weight Mw of the ethylene / α-olefin interpolymer is ≤80,000 g / mol, or ≤75,000 g / mol, or ≤70,000 g / mol, or ≤68,000 g / mol, or ≤66,000 g / mol, or ≤64,000 g / mol, or ≤62,000 g / mol, or ≤60,000 g / mol.

[0129] Z] A composition according to any one of A] to Y] above, wherein the molecular weight distribution (MWD = Mw / Mn) of the ethylene / α-olefin interpolymer is ≥ 1.6, or ≥ 1.7, or ≥ 1.8, or ≥ 1.9, or ≥ 2.0.

[0130] AA] A composition according to any one of A] to Z] above, wherein the molecular weight distribution MWD of the ethylene / α-olefin interpolymer is ≤2.9, or ≤2.8, or ≤2.7, or ≤2.6, or ≤2.5, or ≤2.4, or ≤2.3, or ≤2.2.

[0131] BB] A composition according to any one of A] to AA] above, wherein for the ethylene / α-olefin interpolymer, the α-olefin is C3-C 20 α-olefins, further C3-C 10 α-olefin. CC] A composition according to any one of A] to BB] above, wherein for the ethylene / α-olefin interpolymer, the α-olefin is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further selected from propylene, 1-butene or 1-octene, and further selected from 1-butene or 1-octene, and further selected from 1-octene.

[0132] DD] A composition according to any one of A] to CC] above, wherein the ethylene / α-olefin interpolymer is an ethylene / α-olefin copolymer.

[0133] EE] A composition according to any one of A] to DD] above, wherein the ethylene / α-olefin interpolymer is selected from the following: ethylene / propylene copolymers, ethylene / butene copolymers or ethylene / octene copolymers, and further selected from ethylene / butene copolymers or ethylene / octene copolymers, and further selected from ethylene / octene copolymers.

[0134] FF] A composition according to any one of A] to EE] above, wherein the composition comprises ≥50.0 wt%, or ≥55.0 wt%, or ≥60.0 wt%, or ≥65.0 wt%, or ≥70.0 wt%, or ≥75.0 wt%, or ≥80.0 wt%, or ≥85.0 wt%, or ≥90.0 wt%, or ≥92.0 wt%, or ≥94.0 wt% of the ethylene / α-olefin interpolymer, based on the weight of the composition.

[0135] GG] A composition according to any of A] to FF] above, wherein the composition comprises ≥ 95.0 wt%, or ≥ 95.5 wt%, or ≥ 96.0 wt%, or ≥ 96.5 wt%, or ≥ 97.0 wt%, or ≥ 97.5 wt%, or ≥ 98.0 wt%, or ≥ 98.1 wt% of the ethylene / α-olefin interpolymer, based on the weight of the composition.

[0136] HH] A composition according to any one of A] to GG] above, wherein the composition comprises ≤100.0 wt%, or ≤99.8 wt%, or ≤99.6 wt%, or ≤99.4 wt%, or ≤99.2 wt%, or ≤99.0 wt%, or ≤98.8 wt%, or ≤98.6 wt%, or ≤98.4 wt%, or ≤98.3 wt% of the ethylene / α-olefin interpolymer, based on the weight of the composition.

[0137] II] A composition according to any one of A] to HH] above, wherein the composition further comprises a second ethylene / α-olefin interpolymer, which differs from the ethylene / α-olefin interpolymer in one or more polymer properties, and further differs in one or more properties selected from comonomer content, I2, I10 / I2, Mn, Mw, Mz, MWD, or any combination thereof, and further differs in one or more properties selected from Mn, Mw, Mz, MWD, or any combination thereof.

[0138] JJ] A composition according to II] above, wherein the second ethylene / α-olefin interpolymer has a density from 0.860 g / cc to 0.890 g / cc, or from 0.865 g / cc to 0.888 g / cc, or from 0.865 g / cc to 0.885 g / cc.

[0139] KK] A composition according to II] or JJ] above, wherein the melt index (I2) of the second ethylene / α-olefin interpolymer is from 0.5 g / 10 min to 50 g / 10 min, or from 1.0 g / 10 min to 20.0 g / 10 min, or from 5.0 g / 10 min to 10.0 g / 10 min.

[0140] LL] A composition according to any one of II] to KK] above, wherein for the second ethylene / α-olefin interpolymer, the α-olefin is C3-C 20 α-olefins, further C3-C 10 α-Olefins.

[0141] MM] A composition according to any one of II] to LL] above, wherein for the second ethylene / α-olefin interpolymer, the α-olefin is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and is further selected from propylene, 1-butene or 1-octene, and is further selected from 1-butene or 1-octene, and is further selected from 1-octene.

[0142] NN] A composition according to any one of II] to MM] above, wherein the second ethylene / α-olefin interpolymer is an ethylene / α-olefin copolymer.

[0143] OO] A composition according to any one of II] to NN] above, wherein the second ethylene / α-olefin interpolymer is selected from the following: ethylene / propylene copolymers, ethylene / butene copolymers or ethylene / octene copolymers, and further selected from ethylene / butene copolymers or ethylene / octene copolymers, and further selected from ethylene / octene copolymers.

[0144] PP] A composition according to any one of A] to OO] above, wherein the TGIC width parameter B 1 / 4 ≤7.5, or ≤7.0, or ≤6.5, or ≤6.0, or ≤5.5, or ≤5.0, or ≤4.8, or ≤4.6, or ≤4.4, or ≤4.2, or ≤4.0, or ≤3.8.

[0145] QQ] A composition according to any one of A] to OO] above, wherein the TGIC width parameter B 1 / 4 ≥1.5, or ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.2.

[0146] [RR] The composition according to any one of II] to QQ] above, wherein the composition further comprises a peroxide and a silane coupling agent.

[0147] SS] A composition according to any one of A] to RR] above, wherein the weight ratio of peroxide to silane coupling agent is ≥0.5, or ≥1.0, or ≥1.5, or ≥2.0, or ≥2.5, or ≥3.0, or ≥3.5, or ≥4.0.

[0148] TT] A composition according to any one of A] to SS] above, wherein the weight ratio of peroxide to silane coupling agent is ≤7.0, or ≤6.5, or ≤6.0, or ≤5.5, or ≤5.0, or ≤4.5.

[0149] UU] A composition according to any one of A]-TT] (A to TT) above, wherein the composition further comprises a crosslinking auxiliary agent.

[0150] VV] A composition according to UU] above, wherein the crosslinking aid is present in an amount of ≥0.05 wt%, or ≥0.10 wt%, or ≥0.15 wt%, or ≥0.20 wt%, or ≥0.25 wt%, or ≥0.30 wt%, or ≥0.35 wt%, or ≥0.40 wt%, or ≥0.45 wt%, or ≥0.50 wt%, based on the weight of the composition.

[0151] WW] A composition according to UU] or VV] above, wherein the crosslinking aid is present in an amount of ≤3.00 wt%, or ≤2.50 wt%, or ≤2.00 wt%, or ≤1.50 wt%, or ≤1.00 wt%, or ≤0.80 wt%, or ≤0.70 wt%, or ≤0.60 wt%, based on the weight of the composition.

[0152] XX] A composition according to any one of UU] to WW] above, wherein the weight ratio of peroxide to auxiliary agent is ≥0.5, or ≥0.8, or ≥1.0, or ≥1.1, or ≥1.2, or ≥1.3, or ≥1.4, or ≥1.5, or ≥1.6, or ≥1.8.

[0153] YY] A composition according to any one of UU] to XX] above, wherein the weight ratio of peroxide to auxiliary agent is ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4, or ≤2.3, or ≤2.2, or ≤2.0.

[0154] ZZ]] A composition according to any one of UU]-YY] above, wherein the weight ratio of the auxiliary agent to the silane coupling agent is ≥1.0, or ≥1.2, or ≥1.4, or ≥1.6, or ≥1.8, or ≥2.0. A3] A composition according to any one of UU]-ZZ] above, wherein the weight ratio of the auxiliary agent to the silane coupling agent is ≤3.6, or ≤3.4, or ≤3.2, or ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4.

[0155] B3] A composition according to any one of A] to A3] above, wherein the composition comprises ≥0.05 wt.%, or ≥0.10 wt.%, or ≥0.15 wt.%, or ≥0.20 wt.%, or ≥0.25 wt.%, or ≥0.30 wt.%, or ≥0.35 wt.%, or ≥0.40 wt.%, or ≥0.45 wt.%, or ≥0.50 wt.%, or ≥0.55 wt.%, or ≥0.60 wt.% of peroxide, based on the weight of the composition.

[0156] C3] A composition according to any one of A] to B3] above, wherein the composition comprises ≤5.00 wt.%, or ≤4.50 wt.%, or ≤4.00 wt.%, or ≤3.50 wt.%, or ≤3.00 wt.%, or ≤2.50 wt.%, or ≤2.00 wt.%, or ≤1.50 wt.%, or ≤1.00 wt.% of peroxide, based on the weight of the composition.

[0157] D3] A composition according to any one of A] to C3] above, wherein the composition comprises ≥0.05 wt%, or ≥0.10 wt%, or ≥0.15 wt%, or ≥0.20 wt% of a silane coupling agent based on the weight of the composition.

[0158] E3] A composition according to any one of A] to D3] above, wherein the composition comprises ≤3.00 wt%, or ≤2.50 wt%, or ≤2.00 wt%, or ≤1.50 wt%, or ≤1.00 wt%, or ≤0.80 wt%, or ≤0.60 wt% of a silane coupling agent, based on the weight of the composition.

[0159] F3] A composition according to any one of A] to E3] above, wherein the composition comprises ≥99.0 wt%, or ≥99.1 wt%, or ≥99.2 wt%, or ≥99.3 wt% of the sum of the interpolymer, the peroxide and the silane coupling agent, based on the weight of the composition.

[0160] G3] A composition according to any one of A] to F3] above, wherein the composition comprises ≤100.0 wt%, or ≤99.9 wt%, or ≤99.8 wt%, or ≤99.7 wt%, or ≤99.6 wt%, or ≤99.5 wt% of the sum of the interpolymer, the peroxide, and the silane coupling agent, based on the weight of the composition.

[0161] H3] A composition according to any one of A] to G3] above, wherein the composition further comprises at least one additive selected from UV stabilizers, antioxidants or combinations thereof.

[0162] I3] A composition according to H3] above, wherein the at least one additive is present in an amount of ≥0.01 wt%, or ≥0.02 wt%, or 0.03 wt%, or ≥0.04 wt%, or ≥0.06 wt%, or ≥0.08 wt%, or ≥0.10 wt%, based on the weight of the composition.

[0163] J3] A composition according to H3] or I3] above, wherein the at least one additive is present in an amount of ≤2.00 wt%, or ≤1.50 wt%, or ≤1.00 wt%, or ≤0.80 wt%, or ≤0.60 wt%, or ≤0.40 wt%, or ≤0.20 wt%, based on the weight of the composition.

[0164] K3] A cross-linked composition formed from the composition according to any one of A] to J3] above.

[0165] L3] A composition according to K3] above, wherein the "MH-ML" value of the composition is ≥5.00, or ≥5.10, or ≥5.15, or ≥5.20, or ≥5.22, or ≥5.24, or ≥5.26, or ≥5.28.

[0166] M3] A composition according to K3] or L3] above, wherein the gel content (4+12 min) of the composition is ≥84%, or ≥85%, or ≥86%.

[0167] N3] An article comprising at least one component formed from the composition according to any one of A] to M3] above.

[0168] O3] The article according to N3], wherein the article is a film, and further is an extruded film and / or a cast film, and further is an extruded film.

[0169] P3] The article according to N3], wherein the article is a solar cell module.

[0170] Q3] A method of forming a solar cell module, the method comprising laminating a solar cell array between two film layers, and wherein each film layer is independently formed from a composition according to any one of A] to M3] above.

[0171] R3] The method according to Q3] above, wherein each film layer is formed from the same composition.

[0172] S3] A solution polymerization process for preparing an ethylene / α-olefin interpolymer; the process comprises polymerizing a reaction mixture comprising ethylene, an α-olefin, a solvent and a metal complex selected from the following a) in a reactor at a reactor temperature of ≥150°C:

[0173] a) a biphenol metal complex selected from the following structure 1, as described above in the Summary of the Invention (SOI):

[0174]

[0175] T3] The method according to S3] above, wherein for structure 1, L is -(CH2)n-, wherein n=2 to 4; -CH2C(R a R b )CH2-, where R a and R b Each independently is (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl or -H; or -CH2Ge(R D )2CH2- or –CH2Si(R D )2CH2-, where each R D Independently selected from the group consisting of: -H, (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2.-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )- and (R N )2NC(O)-; and each R in structure 1 C , R P and R N Independently (C1-C 30 ) hydrocarbon group, (C1-C 30 ) heteroalkyl or -H;

[0176] U3] The method according to S3] or T3] above, wherein for structure 1, -Z 1 -and-Z 2 - is -O-. V3] According to the method described in any one of S3] to U3] above, wherein for structure 1, R 1 or R 8 At least one of them is selected from a group having formula (II) or a group having formula (I).

[0177] W3] A method according to any one of S3] to V3] above, wherein for structure 1, R 1 and R 8 are the same and are selected from the group consisting of a group having formula (I), a group having formula (II) and a group having formula (III).

[0178] X3] A method according to any one of S3] to W3] above, wherein for structure 1, R 1 =R 8 = a group having the formula (II).

[0179] Y3] The method according to X3] above, wherein for formula (II) of structure 1, R 43 =R 46 = unsubstituted alkyl, further unsubstituted (C1-C 10 )alkyl, further is unsubstituted (C1-C8)alkyl, further is unsubstituted (C1-C6)alkyl, further is unsubstituted (C1-C4)alkyl, further is tert-butyl.

[0180] Z3] According to the method described above X3] or Y3], wherein for formula (II), R 41 =R 42 =R 44 =R 45 =R 47 =R 48 =H.

[0181] A4] A method according to any one of S3] to Z3] above, wherein for structure 1, L is -CH2C(R a R b )CH2-, where R a and R b Each independently is (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl or -H; or -CH2Ge(R D )2CH2- or –CH2Si(R D )2CH2-, where each R D Independently selected from the group consisting of: -H, (C1-C 40 ) alkyl and (C1-C 40 ) heteroalkyl.

[0182] B4] A method according to any one of S3] to A4] above, wherein for structure 1, L is selected from the following:

[0183] i)-CH2Si(Ra )(R b )CH2- or -CH2Ge(R a )(R b )CH2-, where R a and R b Each independently is (C1-C 30 )alkyl or (C1-C 30 ) heteroalkyl;

[0184] ii) 1,3-dimethylpropane-1,3-diyl;

[0185] iii) bis(methylene)cyclohexane-1,2-diyl;

[0186] iv) propan-1,3-diyl; or

[0187] iv) butane-1,4-diyl.

[0188] C4] A method according to any one of S3] to B4] above, wherein for Structure 1, L is selected from the following:

[0189] i)-CH2Si(R a )(R b )CH2-, where R a and R b are each independently unsubstituted (C1-C 10 )alkyl, further unsubstituted (C1-C8)alkyl, further unsubstituted (C1-C6)alkyl, further unsubstituted (C1-C4)alkyl, further unsubstituted (C1-C3)alkyl;

[0190] ii) 1,3-dimethylpropane-1,3-diyl; or

[0191] iii) Bis(methylene)cyclohexane-1,2-diyl.

[0192] D4] The method according to any one of S3] to C4] above, wherein for structure 1, n=2, and each X is the same and is an unsubstituted alkyl group.

[0193] E4] The method according to D4] above, wherein each X is an unsubstituted (C1-C3) alkyl group, further an unsubstituted (C1-C2) alkyl group, further a methyl group.

[0194] F4] A method according to any one of S3] to E4] above, wherein for Structure 1, R10 = R15.

[0195] G4] A method according to any one of S3] to F4] above, wherein for structure 1, R10=R15=halogen, and further is F.

[0196] H4] A method according to any one of S3] to G4] above, wherein for Structure 1, R3 = R6.

[0197] I4] A method according to any one of S3] to H4] above, wherein for structure 1, R3 = R6 = unsubstituted alkyl.

[0198] J4] A method according to any one of S3] to I4] above, wherein for structure 1, R3 = R6 = unsubstituted (C1-C 12 ) alkyl, further unsubstituted (C1-C 10 )alkyl, further is unsubstituted (C2-C8)alkyl, further is unsubstituted (C4-C8)alkyl, further is unsubstituted C8 alkyl.

[0199] K4] A method according to any one of S3] to J4] above, wherein for structure 1, R2=R4=R5=R7=R9=R11=R12=R13=R14=R16=H.

[0200] L4] According to the method described in any one of S3]-K4] above, wherein for Structure 1, metal M=Zr. M4] According to the method described in any one of S3]-L4] above, wherein Structure 1 is selected from the following Structure (1a) or Structure (1b):

[0201]

[0202] N4] The method according to M4] above, wherein structure 1 is structure (1a).

[0203] O4] According to the method described in S3]-N4], the reaction mixture also includes a co-catalyst-1 comprising a borate and a co-catalyst-2 comprising an aluminoxane.

[0204] P4] According to the method of S3]-O4] above, the total catalyst efficiency of the method at a reactor temperature of ≥155°C, or ≥160°C, or ≥165°C, or ≥170°C, or ≥175°C, or ≥180°C, or ≥185°C, or ≥186°C, or 187°C, or ≥188°C, or ≥189°C, or ≥190°C is ≥2.5×10 6 , or ≥2.6×10 6 , or ≥2.8×10 6 , or ≥3.0×10 6 , or ≥3.2×10 6, or ≥3.4×10 6 , or ≥3.6×10 6 , or ≥3.7×10 6 , or ≥3.8×10 6 , or ≥3.9×10 6 , or ≥4.0×10 6 , or ≥4.1×10 6 , or ≥4.2×10 6 [(g interpolymer) / (g total catalyst metal)].

[0205] Q4] The method according to S3] to P4] above, wherein the total catalyst efficiency of the method at an ethylene / α-olefin interpolymer density of 0.860 g / cc to 0.900 g / cc, or 0.865 g / cc to 0.890 g / cc, or 0.868 g / cc to 0.880 g / cc is ≥ 2.5×10 6 , or ≥2.6×10 6 , or ≥2.8×10 6 , or ≥3.0×10 6 , or ≥3.2×10 6 , or ≥3.4×10 6 , or ≥3.6×10 6 , or ≥3.7×10 6 , or ≥3.8×10 6 , or ≥3.9×10 6 , or ≥4.0×10 6 , or ≥4.1×10 6 , or ≥4.2×10 6 [(g interpolymer) / (g total catalyst metal)].

[0206] R4] The method according to S3] -Q4] above, wherein the method is carried out at a reactor temperature of ≥155°C, or ≥160°C, or ≥165°C, or ≥170°C, or ≥175°C, or ≥180°C, or ≥185°C, or ≥186°C, or 187°C, or ≥188°C, or ≥189°C, or ≥190°C.

[0207] S4] The method according to S3]-R4] above, wherein the method is carried out at a reactor temperature of ≤250°C, or ≤240°C, or ≤230°C, or ≤220°C, or ≤210°C, or ≤200°C.

[0208] T4] According to the method described in any one of S3] to S4] above, the reactor is selected from a continuous stirred tank reactor, a loop reactor or a plug flow reactor (or a tubular reactor), further selected from a continuous stirred tank reactor or a loop reactor, and further selected from a continuous stirred tank reactor.

[0209] U4] According to the method described in any one of S3] to T4] above, the reaction mixture also contains hydrogen (H2).

[0210] V4] A composition comprising an ethylene / α-olefin interpolymer formed by the process described in any one of S3] to U4] above.

[0211] W4] A method for determining the TGIC width parameter B of a polymer composition 1 / x The method comprises a polymer composition comprising one or more olefin-based polymers; the method comprises the steps as described in SOI.

[0212] X4] The method according to W4] above, wherein the composition comprises ≥50 wt%, or ≥60 wt%, or ≥70 wt%, or ≥80 wt%, or ≥85 wt%, or ≥90 wt%, or ≥92 wt%, or ≥94 wt%, or ≥96 wt%, or ≥98 wt%, or ≥99 wt% of one or more olefin-based polymers, based on the weight of the composition.

[0213] Y4] A method according to W4] or X4] above, wherein the composition comprises ≤100 wt%, or ≤99 wt%, or ≤98 wt%, or ≤95 wt% of one or more olefin-based polymers, based on the weight of the composition.

[0214] Z4] A method according to any one of W4] to Y4] above, wherein the composition comprises only one olefin-based polymer.

[0215] A5] The method according to Z4] above, wherein the olefin-based polymer is an ethylene / α-olefin interpolymer, and further an ethylene / α-olefin copolymer.

[0216] B5] According to the method described in any one of W4] to A5] above, the support material contains ≥10 wt%, or ≥20 wt%, ≥30 wt%, or ≥40 wt%, or ≥50 wt%, or ≥60 wt%, or ≥70 wt%, or ≥80 wt%, or ≥85 wt%, or ≥90 wt%, or ≥92 wt%, or ≥94 wt%, or ≥96 wt%, or ≥98 wt%, or ≥99 wt% of graphite, based on the weight of the support material.

[0217] C5] A method according to any one of W4] to B5] above, wherein the support material comprises ≥100 wt%, or ≥99 wt%, or ≥98 wt%, or ≥95 wt%, or ≥90 wt% graphite based on the weight of the support material.

[0218] D5] A method according to any one of W4] to C5] above, wherein for step d) of the method, the temperature is increased from 25°C to 170°C, further increased from 30°C to 165°C, and further increased from 30°C to 160°C.

[0219] E5] According to the method described in any one of W4]-D5] above, wherein the HDPE has a MWD of 2.3 to 3.0, or 2.4 to 2.9, or 2.5 to 2.8, and a weight average molecular weight reported as polyethylene equivalent of 100,000 g / mol to 140,000 g / mol, or 105,000 g / mol to 135,000 g / mol, or 110,000 g / mol to 130,000 g / mol, or 115,000 g / mol to 125,000 g / mol.

[0220] F5] The method according to any one of W4]-E5] above, wherein for the B1 / x value, x=1.5 to 6, further x=2 to 6, further x=3 to 6, further x=4 to 6.

[0221] G5] A method according to any one of W4] to F5] above, wherein the carrier material further comprises a filler.

[0222] Test Method

[0223] MDR Testing

[0224] According to ASTM D5289, the curing characteristics were measured using an Alpha Technologies moving die rheometer (MDR) 2000E at a 0.5 degree arc. For each composition, the MDR was loaded with approximately 4 g of pellets. The MDR was run at 150°C for 30 minutes and a "time to torque" curve was generated at a given interval. The following data from each MDR run was used: MH (dNm), or the maximum torque applied by the MDR during the 30-minute test interval (this usually corresponds to the torque applied at the 30-minute time point); ML (dNm), or the minimum torque applied by the MDR during the 30-minute test interval (this usually corresponds to the torque applied at the beginning of the test interval); and T90 (the time required to reach 90% of the MH value).

[0225] Gel content test

[0226] Each cured film prepared by the lamination method (see the experimental section) was cut into small pieces, "3mm×3mm (about 0.5g sample, Ws)". Then, the sample was packed in a metal mesh (mesh size of 120, weight of Wt1), placed in a 250ml glass bottle filled with 100ml xylene, and left at room temperature for 24 hours. After that, the metal mesh and the sample were transferred to a 500ml flask equipped with a condenser and filled with 350ml xylene. After refluxing in boiling xylene for 5 hours with stirring, the packed sample was taken out of the xylene, placed in a vacuum oven, and then heated in vacuum at 120°C for 2 hours until the sample reached a constant weight. Finally, the sample was weighed together with the metal mesh, and the weight was Wt2. The gel content was calculated by the following equation: Gel content = [(Wt2-Wt1) / Ws]*100%. The xylene used is AR grade with a purity greater than or equal to 99%, a mixture of ortho, meta and para isomers, and may contain ethylbenzene.

[0227] Gel Permeation Chromatography

[0228] The chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment is set at 160°C and the column compartment is set at 150°C. The column is 4 Agilent "Mixed A" 30cm 20 micron linear mixed bed chromatographic columns. The chromatographic solvent is 1,2,4-trichlorobenzene containing 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.

[0229] The GPC column set was calibrated using 21 narrow molecular weight distribution polystyrene standards ranging in molecular weight from 580 to 8,400,000 and arranged in six "cocktail" mixtures with at least ten times intervals between individual molecular weights. The standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, "0.025 grams of polystyrene standards were prepared in 50 milliliters of solvent," and for molecular weights less than 1,000,000, "0.05 grams of polystyrene standards were prepared in 50 milliliters of solvent." The polystyrene standards were gently stirred at 80 degrees Celsius for 30 minutes to dissolve. The polystyrene standard peak molecular weight was converted to polyethylene molecular weight using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):

[0230] M 聚乙烯 =A×(M 聚苯乙烯 ) B (EQ1), where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.

[0231] A fifth order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 Mw.

[0232] Total plate counts for the GPC column set were performed using decane (prepared as 0.04 g in 50 ml TCB and dissolved for 20 minutes under slow stirring). Plate counts (Equation 2) and symmetry (Equation 3) were measured at 200 microliter injections according to the following equations:

[0233] Where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum.

[0234] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum peak position, tenth height is 1 / 10 the height of the peak maximum, and where post-peak refers to the tail of the peak at a later retention volume than the peak maximum, and where pre-peak refers to the front of the peak at an earlier retention volume than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.

[0235] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml, and the solvent (containing 200 ppm BHT) was added to a septum-covered vial previously sparged with nitrogen by a PolymerChar high temperature autosampler. The samples were dissolved at 160 degrees Celsius for 2 hours under "slow" shaking.

[0236] Based on the GPC results, the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer was used, according to Equations 4-6, using the PolymerChar GPCOne TM The software was used to calculate the Mn of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw(GPC) and Mz (GPC) Calculation of. Equation 4-6 is as follows:

[0237]

[0238] and

[0239]

[0240] To monitor the deviation over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any change in the time of the decane marker peak was related to a linear change in the flow rate (flow rate (effective)) for the entire run.

[0241] To facilitate the highest accuracy of RV measurements of the flow marker peak, the peaks of the flow marker concentration chromatogram were fit to a quadratic equation using a least squares fitting procedure. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated as Equation 7: Flow rate (effective) = flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (EQ7).

[0242] By PolymerChar GPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.7% of the nominal flow rate.

[0243] 1H NMR method

[0244] Sample Preparation The samples were prepared by adding approximately 130 mg of sample to 3.25 g of "50 / 50 (by weight) tetrachloroethane-d2 / perchloroethylene with 0.001M Cr(AcAc)3" in a NORELL 1001-7, 10 mm NMR tube. The samples were purged by bubbling N2 through the solvent via a pipette inserted into the tube for approximately five minutes to prevent oxidation. The tubes were then capped, sealed with TEFLON tape, and then soaked overnight at room temperature to promote sample dissolution. The samples were kept in a N2 purge box during storage, before and after preparation to minimize exposure to O2. The samples were heated and vortexed at 115°C to ensure homogeneity.

[0245] Data acquisition parameters and data analysis were performed on a Bruker AVANCE 600 MHz spectrometer equipped with a Bruker high temperature cryoprobe and a sample temperature of 120 °C. 1 H NMR. Two experiments were performed to obtain spectra: a control spectrum for quantification of total polymer protons; and a double presaturation experiment, which suppresses the closely spaced peaks associated with the polymer chains and enables high sensitivity spectra for quantification of end groups. The control was run with ZG pulse, 4 scans, SWH 10,000 Hz, AQ 1.82 s, D1 14 s. The modified pulse sequence lc1prf2.zz, TD 32768, 64 scans, DS2, SWH 9,000 Hz, AQ 1.82 s, D1 2 s, D 13 12s carry out double presaturation experiment.Unsaturation measurement is carried out according to the method described below.Measure the area under the resonance from the polymer chain (that is, CH, CH2 and CH3 in polymer) from the spectrum (control spectrum) obtained during the above-mentioned first experiment.Measure the area under the unsaturation (that is, vinyl, vinylene, trisubstituted vinylene and vinylene) of four key types obtained during the above-mentioned second (presaturation) experiment.Both spectra are normalized to the area under the resonance from the solvent.The mole number of the corresponding unsaturation is calculated by dividing the area under the unsaturated resonance by the number of protons that contribute to the resonance.The mole number of carbon in polymer is calculated by dividing the area under the peak of polymer chain (that is, CH, CH2 and CH3 in polymer) by 2.Then, the amount of total unsaturation is expressed as the relative ratio of the mole number of total unsaturation to the mole number of carbon in polymer, represented by the number of unsaturations per 1000 carbons.

[0246] Melt Index

[0247] The melt index I2 of ethylene-based polymers is measured according to ASTM D-1238 at 190°C / 2.16kg (melt index I10 at 190°C / 10.0kg). I10 / I2 is calculated from the ratio of I10 to I2. The melt flow rate MFR of propylene-based polymers is measured according to ASTM D-1238 at 230°C / 2.16kg.

[0248] Polymer density

[0249] Polymer density is measured according to ASTM D-792.

[0250] High Temperature Thermal Gradient Interaction Chromatography (HT-TGIC or TGIC) - Determination of TGIC Width Parameters

[0251] TGIC measurements were performed using a commercially available crystallization elution fractionation instrument (CEF) (Polymer Char, Spain, Spain) (Cong et al., Macromolecules, 2011, Vol. 44, No. 8, pp. 3062-3072). The CEF instrument was equipped with an IR-5 detector. Graphite was used as a stationary phase in a HT-TGIC column (Freddy, A. Van Damme et al., US 8,476,076; Winniford et al., US 8,318,896). A single graphite column (250×4.6 mm) was used for separation. Graphite was filled into the column using a dry filling technique, followed by a dry filling technique, followed by a wet filling technique (Cong et al., EP 2714226B1 and references cited therein). Graphite (essentially non-porous with high crystallinity) was obtained from Superior Graphite. The experimental parameters were as follows: top oven / transfer tube / needle temperature was 150°C, dissolution temperature was 150°C, dissolution agitation setting was 2, pump stabilization time was 15 seconds, pump flow rate for column cleaning was 0.500 mL / m, pump flow rate for column loading was 0.300 mL / min, stabilization temperature was 150°C, stabilization time (pre, before loading into the column) was 2.0 min, stabilization time (post, after loading into the column) was 1.0 min, SF (soluble fraction) time was 5.0 min, cooling rate from 150°C to 30°C was 3.00°C / min, flow rate during cooling process was 0.04 mL / min, heating rate from 30°C to 160°C was 2.00°C / min, isothermal time at 160°C was 10 min, elution flow rate was 0.500 mL / min and injection loop size was 200 microliters. The flow rate during the cooling process was adjusted according to the length of the graphite column so that all polymer fractions remained on the column at the end of the cooling cycle.

[0252] The sample was prepared by a PolymerChar autosampler with a concentration of 4.0 mg / mL in ODCB maintained at 150°C for 120 minutes. Silica gel 40 (particle size 0.2 mm-0.5 mm, catalog number 10181-3, EMD) was dried at 160°C in a vacuum oven. For a CEF instrument equipped with an autosampler with N2 purging capability, silica gel 40 was filled into two "300 mm × 7.5 mm" GPC-sized stainless steel columns, and silica gel 40 columns were installed at the inlet of the pump of the CEF instrument to dry ODCB. This "ODCB dried with silica gel" is now referred to as "ODCB".

[0253] TGIC data were processed on the PolymerChar (Spain) "GPC One" software platform. Temperature calibration was performed using approximately 2 mg to 6 mg of eicosane, 14.0 mg of isotactic homopolymer polypropylene iPP (molecular weight Mw reported as equivalent to 150,000 g / mol to 190,000 g / mol polyethylene, and a polydispersity (Mw / Mn) of 3.6 to 4.0), with the iPP DSC melting temperature measured at 158°C-159°C (DSC method described below). 14.0 mg of linear homopolymer polyethylene HDPE (zero comonomer content, weight average molecular weight (Mw) reported as equivalent to 115,000 g / mol to 125,000 g / mol polyethylene, and a polydispersity of 2.5 to 2.8) was added to a "10 mL vial" filled with 7.0 mL of ODCB. The dissolution time was 2 hours at 160°C.

[0254] For the calibration method, solutions of eicosane, iPP and HDPE were used. For elution temperatures in the range of 30°C to 150°C, the method consisted of the following steps.

[0255] 1. Extrapolate the elution temperature of each isothermal step during the elution process based on the heating rate (e.g. Figure 1 ). The solid line is the experimental data. The dashed line is the extrapolation of the elution temperature of the two isothermal steps.

[0256] 2. Calculation of delay volume. The temperature (x-axis) is shifted corresponding to the IR measurement channel chromatogram (y-axis) so that the eicosane peak maximum (y-axis) coincides with an elution temperature of 30.0°C. The delay volume is calculated by dividing the temperature difference (30°C - actual elution temperature of the eicosane peak maximum) by the heating rate of the method and then multiplying by the elution flow rate.

[0257] 3. Each recorded elution temperature was adjusted using this same delay volume adjustment.

[0258] 4. It is linearly proportional to the heating rate, so that the HDPE reference is observed to have an elution peak maximum temperature of 150.0°C, while the eicosane elution peak maximum temperature remains at 30.0°C. The TGIC chromatogram of the eicosane / iPP / HDPE mixture is shown in Figure 2 middle.

[0259] At least 20 ethylene octene random copolymers are prepared using a single-site catalyst and have an Mw (ethylene equivalent weight average molecular weight) in the range of 36,000 to 150,000 and a polydispersity (MWD) of 2.0 to 2.2. The elution peak temperature (Tp) of each ethylene octene copolymer and the octene content (wt%) of the copolymer are measured following Figure 3The molecular weight distribution is measured according to the reference (Cong et al., Macromolecules, 2011, Vol. 44, No. 8, pp. 3062-3072). The octene content is measured by 13C NMR according to (Li et al., US 7,608,668 and references cited therein).

[0260] Data processing of polymer samples by HT-TGIC

[0261] A solvent blank (pure solvent injection) was run under the same experimental conditions as the polymer samples. Data processing for the polymer samples included the following: subtraction of the solvent blank for each detector channel, temperature extrapolation as described in the calibration procedure, temperature compensation with the delay volume determined by the calibration procedure, and adjustment of the elution temperature axis to the range of 30°C and 160°C as calculated from the calibrated heating rate.

[0262] The chromatograms (measurement channel of the IR-5 detector) were integrated with the PolymerChar "GPC One" software. A straight baseline was drawn from the visible difference when the peaks were reduced to a flat baseline at high elution temperature (subtracting the approximate zero value in the blank chromatogram) and the minimum or flat region of the detector signal on the high temperature side of the soluble fraction (SF).

[0263] The melting temperature of homopolymer polypropylene represented by the HT-TGIC melting point of iPP was determined using a differential scanning calorimeter (DSC). The temperature at the maximum heat flow rate relative to the linear baseline was used as the melting point. The linear baseline was constructed from the beginning of melting (above the glass transition temperature) to the end of melting. The temperature was increased from room temperature to 200°C at 10°C / min, held at 200°C for 5min; decreased to 0°C at 10°C / min, held at 0°C for 5min; then, the temperature was increased from 0°C to 200°C at 10°C / min; and the data were obtained from the second heating cycle.

[0264] Calculate the width parameter B of the TGIC curve 1 / x

[0265] Here, parameter B 1 / x According to the TGIC measurement definition, the comonomer distribution width of both the comparative sample and the inventive sample is quantified (see e.g. Figure 4 ). The following procedure describes the calculation of B1 / x from TGIC measurements.

[0266] 1. Run the test sample and the eicosane / iPP / HDPE blend in the same run train according to the TGIC method described above.

[0267] 2. Generate a TGIC chromatogram (dwi / dT versus elution temperature (T) curve).

[0268] 3. For the test sample, the maximum height (dwi / dTi versus temperature) of the TGIC chromatogram is obtained by searching for the highest intensity of each data point between 35.0°C and 170.0°C, and the corresponding elution temperature of the TGIC chromatogram at the maximum height is defined as the curve temperature (Tp). In the case where the TGIC chromatogram has multiple peaks (excluding the SF peak) and the multiple peaks have exactly the same peak height, the peak at the highest elution temperature is defined as the curve temperature (Tp). The curve width (at 1 / x of the maximum height) is defined as the temperature difference between the front temperature and the rear temperature at 1 / x of the maximum peak height. The front temperature at 1 / x of the maximum height is searched forward from 35.0°C, while the rear temperature at 1 / x of the maximum height is searched in the opposite direction from 170.0°C.

[0269] 4. HDPE peak width at 1 / x of the HDPE peak height (peak width @ 1 / x) calculated based on the eicosane / iPP / HDPE reference (at 150.0°C elution temperature) (see Figure 2 ). 5.

[0271] Then calculate B based on the following equation 1 / x :

[0272]

[0273] TGIC width parameters (e.g., B 1 / 4 ) is an indication of the breadth of the comonomer distribution of the ethylene / α-olefin interpolymer. The smaller B 1 / 4 A value of 1 indicates a narrower comonomer distribution. It has been found that a narrow comonomer distribution (smaller B 1 / x ) is beneficial to the curing effect of POE in PV encapsulant formulations. TGIC chromatography is an important technique for characterizing the comonomer content and its distribution (see Figure 3 ). The peak width (°C) at a certain portion of the height of the maximum (mass intensity) peak in the TGIC curve can be used to quantify the comonomer distribution width. However, the absolute value of the peak width may also be affected by chromatography-related experimental factors (Stregel et al., "Modern size-exclusion liquid chromatography", Wiley, 2nd edition, Chapter 3) and / or the comonomer content of the resin. In the present case, the comonomer distribution was determined by using B 1 / x The parameters are defined to minimize the deviations from experimental factors and the comonomer content in the polymer.

[0274] experiment

[0275] Commercially available polymers and additives

[0276] Ethylene / 1-octene random copolymer: density 0.873 g / cc, I2 14 g / 10 min (XUS 38669 polyolefin elastomer from The Dow Chemical Company). This copolymer is denoted as "POE669" in the following table.

[0277] ENGAGE 8407 polyolefin elastomer from The Dow Chemical Company, ethylene / 1-octene random copolymer: density 0.870 g / cc, I2 30 g / 10 min. Indicated as POE 407 in the following table.

[0278] TBEC: tert-butyl peroxycarbonate-2-ethylhexyl ester; LUPEROX TBEC organic peroxide from Arkema. VMMS: 3-(trimethoxysilyl)propyl methacrylate; silane coupling agent from Dow Corning. Crosslinking aid: triallyl isocyanurate (TAIC).

[0279] Polymer synthesis and properties

[0280] The interpolymers were each prepared in a one gallon polymerization reactor that was full of liquid and operated under steady state conditions. The catalyst and cocatalyst are listed in Table 1. The solvent, hydrogen, catalyst, and cocatalyst were fed to the reactor according to the process conditions outlined in Tables 2A-2C. The solvent was ISOPAR E provided by ExxonMobil Chemical Company. The reactor temperature was measured at or near the reactor outlet. The interpolymers were separated and pelletized.

[0281] The POE properties are summarized in Table 3. The unsaturation measurements from 1H NMR are summarized in Table 4. The TGIC results are summarized in Table 5.

[0282] Table 1: Catalysts and co-catalysts

[0283]

[0284] * Modified with n-octyl substituents so that the ratio of methyl:n-octyl is about 6:1 and contains 10%-20% trialkylaluminum species

[0285] Table 2A: Reactor Conditions

[0286]

[0287] Table 2B: Catalyst Feed Flow Rates and Efficiencies

[0288]

[0289] * "ppm" amounts based on weight of corresponding catalyst feed solution.

[0290] Table 2C: Cocatalyst Feed Flow Rates

[0291]

[0292] * "ppm" amounts based on weight of co-catalyst feed solution.

[0293] ** "ppm" amount of Al based on the weight of the co-catalyst feed solution.

[0294]

[0295] POE peroxide curing formula

[0296] The POE peroxide curing compositions are shown in Tables 6 and 7. In order to fully mix the peroxide, auxiliary agent and silane into the formulation, the polymer pellets (98.25 wt%) were soaked in a sealable fluorinated high-density polyethylene bottle together with the curing additives (1.00 wt% peroxide, 0.50 wt% crosslinking auxiliary agent and 0.25 wt% silane coupling agent). The soaking (absorption) process was carried out at 50°C for 5 hours until no liquid residue was visible to the naked eye adhering to the bottle. In order to ensure that the peroxide, silane and auxiliary agent were uniformly absorbed by the pellets, the bottle was shaken for 30 seconds every 30 minutes during the absorption process.

[0297] Laminated sample manufacturing

[0298] Two slightly different preparation conditions (A and B below) were used to prepare crosslinked POE films. Each preparation used a PENERGY L036 laminator.

[0299] A) Samples were prepared by lamination using glass substrates (Table 6)

[0300] In the laminator, about "2.5g pellet sample" absorbed with peroxide, silane and auxiliary agent was placed on a PTFE membrane (0.24mm thickness) on top of a glass substrate (3mm thickness). A metal frame with "1mm thickness" was placed around the sample as a spacer to ensure that the cross-linked POE had a thickness of about 1mm. Then another PTFE membrane (0.24mm thickness) was placed on top of the sample. Lamination was carried out at a set temperature of 150°C. The heating method included the following two steps: the first step - preheating without pressure for 4 minutes under vacuum (-100kPa); and the second step - keeping at 1 bar pressure for 12 minutes. After the lamination cycle, the cross-linked membrane was taken out for further gel measurements.

[0301] B) Samples prepared by lamination method using glass substrate (Table 7)

[0302] In the laminator, about "2.5g pellet sample" absorbed with peroxide, silane and auxiliary agent is placed on a PTFE film (0.24mm thickness) on top of a metal substrate (1.8mm thickness). A PTFE frame with "0.5mm thickness" is placed around the sample as a spacer to ensure that the cross-linked POE has a thickness of about 0.5mm. Then another PTFE film (0.24mm thickness) is placed on top of the sample. Lamination is carried out at a set temperature of 150°C. The heating method includes the following two steps: the first step - preheating without pressure for 4 minutes under vacuum (-100kPa); and the second step - keeping at 1 bar pressure for 10 minutes or 16 minutes. After the lamination cycle, the cross-linked film is taken out for further gel measurement.

[0303] Measurement of adhesion to glass after lamination

[0304] Films (100 mm x 150 mm x 0.5 mm) were prepared by compression molding the formulated resin pellets using a Lab Tech LP-S-50 compression molding machine, using the following conditions: preheating at 100°C for 4 minutes without pressure; and holding at 100 MPa and 100°C for 2 minutes. After molding, the film was placed on a glass substrate (dimensions of 100 mm x 150 mm x 3 mm) and then covered with a polyester backing sheet. The sample was then subjected to a lamination process (laminator SHUNHONG SH-X-1000) at 150°C using the following conditions: preheating at vacuum (-100 kPa) for 4 minutes without pressure; and holding at 1 bar pressure for 16 minutes.

[0305] After lamination, the laminated film and backsheet were further cut and separated into three pieces, each piece being "1 inch wide" and "150 mm long" by pulling out the laminated film and backsheet from the glass substrate using INSTRON 5565, and the three specimens were subjected to "180° peel test". The average of the three results was reported.

[0306] Summary of results

[0307] For the PV encapsulation film manufacturing process, the processing performance of the formulated material is limited by the shear heating of the polymer during extrusion. Since the peroxide in the PV encapsulation film formulation decomposes and crosslinks with the POE at temperatures above 110°C, the RPM and resin extrusion rate cannot exceed a threshold that will cause the resin melt temperature to be much higher than 110°C. It is well known that higher melt index POE (i.e., POE with lower viscosity) can have improved processing performance or throughput in the extruder due to lower viscosity and reduced shear heating. In this case, both the comparative sample and the inventive sample were selected to have a relatively high melt index to ensure good processing performance of the formulation. However, for high melt index resins, the crosslinked film typically has a relatively low degree of cure. Therefore, it becomes critical to improve the curing effect of these high melt index resins.

[0308] For a cure comparison between POEs with different unsaturation levels, the cure effects of formulations containing POEs with comparable melt index / processing properties, density, MWD, and comonomer distribution were examined (see Table 6). Here, Inventive Example 1 was compared with Comparative Example 1 (POE with a melt index of approximately 14 dg / min), and Inventive Example 2 was compared with Comparative Example 2 (POE with a melt index of approximately 30 dg / min). The inventive compositions containing the high unsaturation POE clearly showed improved (greater) MDR torque variation (MH-ML) and greater gel content after "4+12min" vacuum lamination.

[0309] The results of Table 7 compare the curing effects of the encapsulation film formulations formed from the POEs. The films formed from the compositions of the present invention (POEs having narrow MWD, narrow comonomer distribution in addition to high unsaturation) provide the best curing performance, with improved MDR torque variation (MH-ML) and greater gel content after "4+10min" vacuum lamination and after "4+16min" vacuum lamination. It is also worth noting that the compositions of the present invention (POEs containing higher vinyl fractions in total unsaturation, higher vinyl / vinylidene ratios, and narrower comonomer distribution) have good adhesion to glass.

[0310] Table 6: Formulation and curing properties

[0311] Comparative Example 1 Comparative Example 2 Invention Example 1 Invention Example 2 POE 669 98.25 POE 407 98.25 POEB 98.25 POE A 98.25 TBEC 1.00 1.00 1.00 1.00 VMMS 0.25 0.25 0.25 0.25 TAIC 0.50 0.50 0.50 0.50 total 100 100 100 100 ML(dNm) 0.07 0.01 0.06 0.02 MH(dNm) 4.07 2.75 6.15 5.31 MH-ML 4.00 2.74 6.09 5.29 T90(min) 11.1 12.1 12.5 13.5 Gel content, 4+12min* 84.99% 79.27% 89.88% 86.12%

[0312] *Samples were prepared by lamination method using glass substrate

[0313] Table 7: Formulation and curing properties

[0314] Comparative Example 3 Comparative Example 4 Comparative Example 5 Invention Example 3 POE 407 98.25 POE D 98.25 POE C 98.25 POE A 98.25 TBEC 1.00 1.00 1.00 1.00 VMMS 0.25 0.25 0.25 0.25 TAIC 0.50 0.50 0.50 0.50 total 100 100 100 100 ML(dNm) 0.02 0.1 0.02 0.03 MH(dNm) 3.02 2.4 4.04 5.37 MH-ML 3.00 2.3 4.02 5.34 T90(min) 12.2 13.3 13.8 13.5 Gel content, 4+10min* 71.72% 66.15% 69.92% 74.99% Gel content, 4+16min* 81.30% 81.28% 88.20% 92.30% Glass adhesion, 4+16min (N / cm) - - 46.0 69.9

[0315] *Samples were prepared by lamination method using metal substrates.

Claims

1. A composition comprising an ethylene / α-olefin interpolymer, wherein the interpolymer comprises the following properties: a) Total unsaturation / 1000C ≥ 0.30; b) Molecular weight distribution MWD ≤ 3.0; c) Thermal gradient interaction chromatography TGIC width parameter B 1 / 4 ≤8.0, wherein the TGIC breadth parameter B of a polymer composition comprising one or more olefin-based polymers is determined 1 / x The method comprises the following steps: a) dissolving the polymer composition in an organic solvent to form a polymer solution; b) injecting at least a portion of the polymer solution onto a column comprising a support material comprising graphite; c) cooling the support material at a rate greater than or equal to 0.1° C. / min; d) increasing the temperature of the support material to elute the polymer of the polymer composition; e) Generate a "dwi / dT versus temperature" curve; f) For the maximum height of the "dwi / dTi vs. temperature" curve, calculate the width of the curve at 1 / x of the maximum height, where x>1; g) determine the temperature at which the curve has the maximum height (Tp); h) calculating the HDPE peak width at 1 / x of the HDPE peak height at an elution temperature of 150.0° C. (peak width @1 / x) based on an eicosane / iPP / HDPE reference; and wherein the reference is analyzed by TGIC according to steps a) to g); i) Calculate B based on the following equation 1 / x : The ethylene / α-olefin interpolymer is prepared by polymerizing ethylene, a C3-C4-olefin copolymer which is octene, and a C5-C6-olefin copolymer which is octene in a reactor at a reactor temperature of ≥150°C. 10 Prepared by a reaction mixture of aliphatic alpha-olefin, a cocatalyst, a solvent and a metal complex; The metal complex is 6',6"'-(propane-1,3-diylbis(oxy))bis(3-(3,6-di-tert-butyl-9H-carbazole-9-yl)-3'-fluoro-5-(2,4,4-trimethylpentan-2-yl)-[1,1'-biphenyl]-2-ol)dimethyl-zirconium, the solution flow rate of the metal complex is 0.42 lb / hr and the solution metal concentration of the metal complex is 2.15 ppm, and the cocatalyst is modified methylaluminoxane (MMAO) 3A type and methyldi(C)tetrakis(pentafluorophenyl)borate 14-18 alkyl) ammonium salts, methyl di(C 14-18 The solution flow rate of the alkyl) ammonium salt was 0.46 lb / hr and the methyl di(C 14-18 The solution concentration of the modified methylaluminoxane (MMAO) 3A type was 30.8 ppm, the solution flow rate of the modified methylaluminoxane (MMAO) 3A type was 0.39 lb / hr and the solution metal concentration of the modified methylaluminoxane (MMAO) 3A type was 34.7 ppm Al; or wherein the metal complex is 6',6"'-(propane-1,3-diylbis(oxy))bis(3-(3,6-di-tert-butyl-9H-carbazole-9-yl)-3'-fluoro-5-(2,4,4-trimethylpentan-2-yl)-[1,1'-biphenyl]-2-ol)dimethyl-zirconium, the solution flow rate of the metal complex is 0.49 lb / hr and the solution metal concentration of the metal complex is 2.15 ppm, and the cocatalyst is modified methylaluminoxane (MMAO) 3A type and methyldi(C)tetrakis(pentafluorophenyl)borate 14-18 alkyl) ammonium salts, methyl di(C 14-18 The solution flow rate of the alkyl) ammonium salt was 0.54 lb / hr and the methyl di(C 14-18 The solution concentration of the modified methylaluminoxane (MMAO) 3A form was 30.8 ppm, the solution flow rate of the modified methylaluminoxane (MMAO) 3A form was 0.22 lb / hr and the solution metal concentration of the modified methylaluminoxane (MMAO) 3A form was 34.7 ppm Al.

2. The composition of claim 1, wherein the ethylene / α-olefin interpolymer has a density ≥ 0.860 g / cc.

3. The composition of claim 1, wherein the ethylene / α-olefin interpolymer has a density of ≤ 0.900 g / cc.

4. The composition of claim 2, wherein the ethylene / α-olefin interpolymer has a density of ≤ 0.900 g / cc.

5. The composition according to any one of claims 1 to 4, wherein the interpolymer further comprises ≥ 5×10 3 The product of [(vinyl / 1000C)*(Mn)] in g / mol.

6. The composition of any one of claims 1 to 4, wherein the interpolymer further comprises a ratio of [(vinyl / 1000C) / (vinylidene / 1000C)] ≥ 2.

0.

7. The composition of any one of claims 1 to 4, wherein the ethylene / α-olefin interpolymer further comprises a % vinyl group of ≥ 50%.

8. The composition according to any one of claims 1 to 4, wherein the composition further comprises a peroxide and a silane coupling agent.

9. The composition according to any one of claims 1 to 4, wherein the composition further comprises a crosslinking aid.

10. An article comprising at least one component formed from the composition of any one of claims 1 to 9.

11. The article of claim 10, wherein the article is a film.

12. The article of claim 10, wherein the article is a solar cell module.

13. A solution polymerization process for preparing an ethylene / α-olefin interpolymer; the process comprising polymerizing, in a reactor at a reactor temperature of ≥150°C, a C3-C4 copolymer containing ethylene, octene, 10 a reaction mixture of an aliphatic alpha-olefin, a cocatalyst, a solvent and a metal complex; The metal complex is 6',6"'-(propane-1,3-diylbis(oxy))bis(3-(3,6-di-tert-butyl-9H-carbazole-9-yl)-3'-fluoro-5-(2,4,4-trimethylpentan-2-yl)-[1,1'-biphenyl]-2-ol)dimethyl-zirconium, the solution flow rate of the metal complex is 0.42 lb / hr and the solution metal concentration of the metal complex is 2.15 ppm, and the cocatalyst is modified methylaluminoxane (MMAO) 3A type and methyldi(C)tetrakis(pentafluorophenyl)borate 14-18 alkyl) ammonium salts, methyl di(C 14-18 The solution flow rate of the alkyl) ammonium salt was 0.46 lb / hr and the methyl di(C 14-18 The solution concentration of the modified methylaluminoxane (MMAO) 3A type was 30.8 ppm, the solution flow rate of the modified methylaluminoxane (MMAO) 3A type was 0.39 lb / hr and the solution metal concentration of the modified methylaluminoxane (MMAO) 3A type was 34.7 ppm Al; or wherein the metal complex is 6',6"'-(propane-1,3-diylbis(oxy))bis(3-(3,6-di-tert-butyl-9H-carbazole-9-yl)-3'-fluoro-5-(2,4,4-trimethylpentan-2-yl)-[1,1'-biphenyl]-2-ol)dimethyl-zirconium, the solution flow rate of the metal complex is 0.49 lb / hr and the solution metal concentration of the metal complex is 2.15 ppm, and the cocatalyst is modified methylaluminoxane (MMAO) 3A type and methyldi(C)tetrakis(pentafluorophenyl)borate 14-18 alkyl) ammonium salts, methyl di(C 14-18 The solution flow rate of the alkyl) ammonium salt was 0.54 lb / hr and the methyl di(C 14-18 The solution concentration of the alkyl) ammonium salt was 30.8 ppm, the solution flow rate of the modified methylaluminoxane (MMAO) 3A type was 0.22 lb / hr and the solution metal concentration of the modified methylaluminoxane (MMAO) 3A type was 34.7 ppm Al; wherein the ethylene / α-olefin interpolymer comprises the following properties: a) Total unsaturation / 1000C ≥ 0.30; b) Molecular weight distribution MWD ≤ 3.0; c) Thermal gradient interaction chromatography TGIC width parameter B 1 / 4 ≤8.0, wherein the TGIC breadth parameter B of a polymer composition comprising one or more olefin-based polymers is determined 1 / x The method comprises the following steps: a) dissolving the polymer composition in an organic solvent to form a polymer solution; b) injecting at least a portion of the polymer solution onto a column comprising a support material comprising graphite; c) cooling the support material at a rate greater than or equal to 0.1° C. / min; d) increasing the temperature of the support material to elute the polymer of the polymer composition; e) Generate a "dwi / dT versus temperature" curve; f) For the maximum height of the "dwi / dTi vs. temperature" curve, calculate the width of the curve at 1 / x of the maximum height, where x>1; g) determine the temperature at which the curve has the maximum height (Tp); h) calculating the HDPE peak width at 1 / x of the HDPE peak height at an elution temperature of 150.0° C. (peak width @1 / x) based on an eicosane / iPP / HDPE reference; and wherein the reference is analyzed by TGIC according to steps a) to g); i) Calculate B based on the following equation 1 / x :

14. The process according to claim 13, wherein the total catalyst efficiency of the process at a reactor temperature of ≥150°C is ≥2.5×10 6 [(g interpolymer) / (g total catalyst metal)].

15. The process of any one of claims 13 to 14, wherein the total catalyst efficiency of the process at an ethylene / α-olefin interpolymer density of 0.860 g / cc to 0.900 g / cc is ≥ 2.5×10 6 [(g interpolymer) / (g total catalyst metal)].

Citation Information

Patent Citations

  • Solar battery encapsulant and solar battery module

    EP2637217B1

  • Resin composition for solar cell sealing materials, solar cell sealing material using same, and solar cell module

    EP2958151B1

  • Resin composition for solar cell sealing material and solar cell sealing material using the same, and solar cell module

    JP2012009688A

  • Ethylene / alpha-olefins block interpolymers

    US7608668B2

  • Chromatography of polyolefin polymers

    US8318896B2